Penyelesaian kes kemalangan jalan raya menurut Undang-Undang Malaysia dan perundangan Islam: Kajian perbandingan / Shahidra Abdul Khalil - Shahidra , Abdul Khalil (2015)
The majority of negligence cases being adjudicated in the Malaysian courts are cases involving road accidents. The settlement process is being criticized by some analysts due to the fact that the litigation process is time consuming. Compensation payouts by insurance companies do not cover all kinds of victims. As a consequence, a proposal to amend the law has been suggested by some researchers including a renewal based on the no-fault liability scheme as practised by other countries. An amendment to the Civil Law Act 1956 has been done in order to improve some aspects in solving of cases. However, it is not able to solve the various problems that arise. Hence, this study puts forward the solution to road accident cases based on Islamic law. The similarities and differences between Islamic law and the law in Malaysia were analysed in order to find the solution to this problem. The comparisons focus on three aspects, which are, determining liability, quantum of compensation and burden of liability. This study employs the library method and a structured interview on a purposive sample. The data analysis was done inductively, deductively and comparatively. The findings show that in Malaysia, it is very complex to prove negligence in cases of road accidents because proving a case depends on the elements to be proven. The quantum of compensation is done based on estimation, especially for cases regarding future loss. These laws which are unclear result in long periods of appeals from the litigation parties. This contributes to late settlement of cases. The findings of this study show otherwise in Islamic law where basically, the method of determining liability is based on the type of action. Therefore, the act of determining libility is clear and also easier because evidence of negligence is not applicable in all situtions. The quantum of compensation according to Islam is based on the use of diat as the ceiling value for various types of losses and self-injuries. Also, the scope for burden of liabilty on ‘aqilah and bayt al-mal in Islamic law is wider as it covers all victims whose rights were wrongly assaulted. Finally, the findings of this study concludes that the Islamic law concept should be applied in order to expedite the settlement of accident cases in Malaysia and to give an overall protection of rights to the victims. It is hoped that this study will contribute significantly to the lawmakers in their efforts to enhance the settlement process of road accidents in Malaysia.